TARGETED THERAPY AND INFECTIONS IN RHEUMATIC DISEASES - B. S. Belov; M. S. Naumtseva; G. M. Tarasova; D. V. Bukhanova (Современная ревматология, 2016)
In the past decade, rheumatology has shown clear progress in the practical introduction of biological agents (BAs) and targeted sintetic anti-inflammatory agents. At the same time, the use of these agents is associated with an increasing risk for infections of different origin and sites, including opportunistic infections (invasive my-coses, Pneumocystis pneumonia, etc.), as well as an increased risk for reactivation of latent infections, primarily tuberculosis (TB). In addition, there are cases of severe infections (pneumonia, sepsis, bacterial arthritis, skin and soft tissue lesions, etc.), including those with a fatal out-come. The review analyzes the literature data (mainly in the last 5 years) regarding the frequency and localization of infections in rheumatologic patients treated with BAs. It characterizes the significance of various infections (TB, pneumonia, chronic viral hepatitis, herpesvirus infection, etc.) in the tactics of following up these patients. The authors emphasize the need for the more widespread use of various vaccines (especially those against influenza and pneumococcal infection) in patients with autoimmune inflammatory rheumatic diseases.